STRATEGY IMPROVING THE QUALITY OF MADRASA EDUCATION - Hasan, Muhammad Zuhdi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the strategy for improving the quality of education at Madrasah Ibtidaiyah Zainul Anwar Alassumur Kulon, Kraksaan, Probolinggo, East Java. To find out these objectives, a qualitative research approach is used with descriptive methods. Data collection techniques are carried out through observation, interviews and documentation studies. While the data analysis procedure is done by Data Reduction, Data Presentation, and Data Verification. From this research activity, an overview was obtained: (1) the madrasah head in improving the quality of madrasah education first planned a program by analyzing the needs of the activities needed by students, educators and education staff to be carried out, planning the curriculum to be implemented, planning policies for adding learning activities; (2) create an organizational structure that involves madrasah stakeholders and complete the required infrastructure; (3) Leaders set a good example at work, motivate and reward personnel both morally and materially, improve welfare, involve educators and education staff in training and education and motivate teachers to have a high enthusiasm for learning; (4) supervising output, PBM, and students in the process of activities in madrasas. (5) the obstacles experienced are personnel who are still not disciplined and consistent with joint decisions, lack of facilities and infrastructure to support activities, there are teachers who do not make use of existing media, weak institutional economics, stakeholders in fulfilling facilities and infrastructure have not been able to help